Investigation and analysis of the linkage mechanism and whole process cost of livestock manure organic fertilizer - Dong, Shanshan; Sui, Bin; Shen, Yujun; Meng, Haibo; Zhao, Lixin; Ding, Jingtao; Zhou, Haibin; Zhang, Xi; Cheng, Hongsheng; Wang, Jian; Li, Ran; Song, Liqiu; et al. (International Journal of Agricultural and Biological Engineering, 2020)
In recent years, the utilization of manure resources for livestock and poultry farming has attracted a widespread attention, and manure resources utilization models suitable for different regional characteristics have formed gradually. Among them, the production of organic fertilizer from animal manure is a vital utilization method. However, there are still some problems such as high production costs, difficult sales, and the unwillingness of farmers to use organic fertilizers which have affected the breeding cycle and the sustainability of manure treatment in livestock and poultry breeding. This article selected 371 organic fertilizer plants, related farms and farmers in China, focusing on the main links of the entire process of livestock manure-organic fertilizer-farm application, and studied the mode of animal manure collection by organic fertilizer plants. The costs of organic fertilizer production and farmland application were discussed. Moreover, suggestions were made for the promotion and implementation of large-scale organic fertilizers to make good utilization of manure resources in livestock and poultry farming.Keywords: livestock manure, organic fertilizer, compost, production cost, application costDOI: 10.25165/j.ijabe.20201302.Citation: Dong S S, Sui B, Shen Y J, Meng H B, Zhao L X, Ding J T, et al. Investigation and analysis of the linkage mechanism and whole process cost of livestock manure organic fertilizer. Int J Agric & Biol Eng, 2020; 13(2): 223–227.